Back Cover: Strong Exchange Coupling in a Trimetallic Radical‐Bridged Cobalt(II)‐Hexaazatrinaphthylene Complex (Angew. Chem. Int. Ed. 18/2016). Issue 18 (24th March 2016) - Moilanen, Jani O.; Chilton, Nicholas F.; Day, Benjamin M.; Pugh, Thomas; Layfield, Richard A.
Abstract : The hexaazatrinaphthylene radical anion is synthesized as a stable potassium salt and transferred intact to Co II as described by R. A. Layfield et al. in their Communication on page 5521 ff. The image depicts a potassium‐crown "flying saucer" beaming down an electron to the HAN ligand in a trimetallic cobalt(II) complex. The impact of reducing the HAN ligand in this way is to dramatically strengthen the exchange coupling within the radical‐bridged molecular magnet.